Altered brain hemodynamic response and cognitive function after sleep deprivation: a functional near-infrared spectroscopy study. Issue 1 (31st December 2023) - Ji, Katherine; Chen, Donna Y.; Karunakaran, Keerthana Deepti; Biswal, Bharat B.
Abstract: Aim: Acute sleep deprivation has revealed altered executive cognitive functioning, including attention, working memory, and interference resolution. In the present study, we investigated brain hemodynamics and cognitive function measures using functional near-infrared spectroscopy (fNIRS). Methods: fNIRS was used to record cortical brain activity in a resting state scan, flanker task, and n-Back tasks under well-rested (WR, >6.5 h sleep for ≥3 days) and sleep-deprived conditions (SD, 28 h awake) in a repeated-measures study in 20 participants (7 female, mean age 20.1 ± 0.413). Results: Our results indicate decreased accuracy rates in the flanker task in the SD condition, suggesting reduced response inhibition capacity. In the flanker task, a significant increase of beta estimates was observed in the SD condition in the right dl-PFC, suggesting potential compensation (BH-FDR corrected p = 0.0418, t (19) = 3.51). There were no significant differences between WR and SD in n-back task accuracy rates or reaction times or in Flanker task reaction times. Otherwise, functional connectivity strengths were not significantly different between the WR and SD sessions on a group-level analysis for the resting state and all tasks (BH-FDR correction, p > 0.05). Conclusion: Our results provide insight into how insufficient sleep patterns affect interference resolution, and that fNIRS can reveal functional connectivity differences inter- and intra-individually in SD conditions.